National medical specialty guidelines of HIV indicator conditions in Europe lack adequate HIV testing recommendations: a systematic guideline review - Jordans, Carlijn C.E.; Vasylyev, Marta; Rae, Caroline; Jakobsen, Marie Louise; Vassilenko, Anna; Dauby, Nicolas; Grevsen, Anne Louise; Jakobsen, Stine Finne; Raahauge, Anne; Champenois, Karen; Papot, Emmanuelle; Malin, Jakob J.; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2022)
BackgroundAdequate identification and testing of people at risk for HIV is fundamental for the HIV care continuum. A key strategy to improve timely testing is HIV indicator condition (IC) guided testing.AimTo evaluate the uptake of HIV testing recommendations in HIV IC-specific guidelines in European countries.MethodsBetween 2019 and 2021, European HIV experts reviewed guideline databases to identify all national guidelines of 62 HIV ICs. The proportion of HIV IC guidelines recommending HIV testing was reported, stratified by subgroup (HIV IC, country, eastern/western Europe, achievement of 90-90-90 goals and medical specialty).ResultsOf 30 invited European countries, 15 participated. A total of 791 HIV IC guidelines were identified: median 47 (IQR: 38-68) per country. Association with HIV was reported in 69% (545/791) of the guidelines, and 46% (366/791) recommended HIV testing, while 42% (101/242) of the AIDS-defining conditions recommended HIV testing. HIV testing recommendations were observed more frequently in guidelines in eastern (53%) than western (42%) European countries and in countries yet to achieve the 90-90-90 goals (52%) compared to those that had (38%). The medical specialties internal medicine, neurology/neurosurgery, ophthalmology, pulmonology and gynaecology/obstetrics had an HIV testing recommendation uptake below the 46% average. None of the 62 HIV ICs, countries or medical specialties had 100% accurate testing recommendation coverage in all their available HIV IC guidelines.ConclusionFewer than half the HIV IC guidelines recommended HIV testing. This signals an insufficient adoption of this recommendation in non-HIV specialty guidelines across Europe.